2013
DOI: 10.13172/2052-0077-2-6-643
|View full text |Cite
|
Sign up to set email alerts
|

Accessory iliacus muscle with splitting of the femoral nerve: a case report

Abstract: Introduction Variations in the iliopsoas muscle complex certainly have some clinical importance. Because these variations are usually associated with unusual femoral nerve formation, here we report a case of variation in the iliacus muscle combined with variation in the femoral nerve. Case report Variation in the iliacus muscle combined with variation in the femoral nerve was observed while performing a routine dissection of a 65-year-old male cadaver in the Department of Anatomy, SRM Medical College. The acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
1
0
1
Order By: Relevance
“…In the current study, as the PLfn passes underneath the IMM, there is a potential risk of nerve compression. Any pathology of IM or IMM may disrupt the function of the femoral nerve and subsequently may result in wasting of the quadriceps and paraesthesia in the anterior and middle compartments of the thigh (Aristotle et al, 2013). Few studies (Galzio et al, 1983;Jelev et al, 2005) have reported IM hematoma and IMM abscess: assuming that could make the PLfn more vulnerable to entrapment.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, as the PLfn passes underneath the IMM, there is a potential risk of nerve compression. Any pathology of IM or IMM may disrupt the function of the femoral nerve and subsequently may result in wasting of the quadriceps and paraesthesia in the anterior and middle compartments of the thigh (Aristotle et al, 2013). Few studies (Galzio et al, 1983;Jelev et al, 2005) have reported IM hematoma and IMM abscess: assuming that could make the PLfn more vulnerable to entrapment.…”
Section: Discussionmentioning
confidence: 99%
“…Jelev y sus colaboradores 2 reportan un músculo iliopsoas accesorio entre 108 autopsias efectuadas durante 22 años. Las anomalías del psoas iliaco se localizan más frecuentemente a nivel de su inserción distal; 3 a veces, estas variaciones anatómicas pueden ser sintomáticas (como en el caso presentado), ocasionando compresión radicular de L4 y/o L5 a nivel extraforaminal 4 o afección del nervio femoral, 5 que requieren ser estudiadas como parte del diagnóstico diferencial de compresión radicular.…”
Section: Wwwmedigraphicorgmxunclassified